COVID-19 With Preexisting Hypercoagulability Digestive Disease - Jiang, Mingshan; Mu, Jingxi; Shen, Silan; Zhang, Hu (Frontiers in Medicine, 2021)
The outbreak of coronavirus disease of 2019 (COVID-19) has become a global public health and economic crisis. The advent of hypercoagulability and thrombotic complications can substantially influence the prognosis of COVID-19 patients. In this review, we elaborate on the clinical findings, potential underlying pathogenesis, and therapeutic strategy of hypercoagulability and thromboembolism in COVID-19, particularly focusing on the COVID-19 patients with preexisting digestive hypercoagulability disease.